PREDICTION OF FAKE PROFILES USING CLASSIFICATION ALGORITHM - Menariya, Bhavini; Vidhya, R (International Journal of Psychosocial Rehabilitation, 2020)
Online Social Networks are progressively affecting the manner in which individuals speak with one another and share data. The expanding protection dangers in social networking sites is drawing in security scientists attempting to recognize and relieve dangers to singular clients. With numerous online social networking sites having tens or many million clients all things considered creating billions of individual information content that can be abused, identifying and forestalling assaults on singular client security is a significant test. The greater part of the flow explore has concentrated on securing the protection of a current online profile in a given online social networking site.The proposed system aims to find the fake profiles using machine learning classification algorithm such as Random Forest that is highly employed. Algorithm has been developed in order to detect the fake profiles based on the dataset. Here the fake profiles are identified before anyone suffer by the suspicious account.